(3HgLI GdYTGb hQhVI GdeTJGbs - (3eMeO Hf CMeO eGejI GdQhej, eGejI GdGfLTGQj,J (B988 (3g` s
(3ChdgG (B:s
(3CeG HYO(B: (3jbhd eG SGdJ Cf jQRbfi Gddg EdG afGf Hafi GdfXGe GdYdi Cf Cchf efJXeG ai Sdc GdfXGe aYQafi HfTQ GdeYQaI , hcfJJ efcQ GdMGd , hejRfi Hjf GdSGOI hGdTYQGA GdehGdi s
(3BNQgG (B:s
(3hdg QMeI Gddg (B: (3GdThb CSgQ ebdJi hGdYTb ZjQ MGdJi s
(3fSNI KGfjIs
(3hgfGc Tc ai Cf eDda GdeNWhW gh cGJHgG fGTNgGs
(3hGdNHQ fGbY ai HYV GdUaMGJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7s
(3GdLRA (B1 - (3U (B809 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B129 s
Keywords: (3GdCOHs